Pengaruh Efikasi Diri Generasi Milenial dan Motivasi terhadap Keputusan Berwirausaha di Bidang Industri Kreatif Kuliner - Setia Budi, M. Arief (Jurnal Salingka Nagari, 2026)
This research is to determinan the influence of self-efficacy and motivation of the millennial generation onentrepreneurial decisions in the creative culinary industry in the city of Banda Aceh. This research meyhod uses a quantitative approach. The total sample for this research was 200 respondents. Research data was collected through questionnaires which analyzed with SPSS through multiple linier regression. The results of this research are based on the avidence in this research,the self-efficacy of the millennial generation partially influences entrepreneurial decisions. However, motivation does not partially influence entrepreneurial decision. Simultaneously, the self-effecacy and motivationof the millennial generation have a significant influence on entrepreneurial decision in the culinary creative industry in the city of Banda Aceh.